Determinants of Blood Donation Status in Malaysia: Profiling the Non-Donors, Occasional Donors, and Regular Donors Determinants of Blood Donation Status in Malaysia: Profiling the Non-Donors, Occasional Donors, and Regular Donors - Lim Mei Ling; Thock Sheng Hui; Andrew K. G. Tan; Gwee Sai Ling (Kajian Malaysia, 2018)
The blood shortage situation is a perennial concern in Malaysia. This study examines the sociodemographic and lifestyle related factors associated with blood donation status of non-donors, occasional donors, and regular donors. Discerning the donation status of blood donors is important as studies have noted that it is more cost-effective to reactivate occasional (consisting of existing or former) donors than to recruit new donors. Based on stratified random sampling measures, primary data were obtained from 550 Malaysian adults aged 18–60 years from Pulau Pinang, Malaysia. Ordered probit analysis was conducted and marginal effects of various factors on blood donation status calculated. Results indicate that sociodemographic factors associated with donor status include gender, marital status, education level, and income level. Lifestyle related factors affecting donor status comprise working hours, family history, and fear of the donation process. It is concluded that donor awareness and education programs should be focused on females, singles, and individuals in the lower socioeconomic echelons. Donor recipients. Measures should be implemented to accommodate busy people and those fearful of the donation process. These strategies could be undertaken not only in Malaysia but also in other countries with comparable sociodemographic and health care settings.